Case Report: ProRoot MTA degradation in a compromised tooth: secondary trauma and acidic microenvironment leading to retreatment with Biodentine - Drukteinis, Saulius; Bilvinaitė, Goda; Galler, Kerstin Martina (2025)
Background: Dental trauma can jeopardize the long-term success of previous endodontic treatments, especially in teeth affected by orthodontically induced inflammatory root resorption (OIIRR). This case presents the first documented association between secondary trauma-induced acidity and degradation of ProRoot mineral trioxide aggregate (MTA) in such compromised teeth. Case presentation: A 20-year-old male with a history of orthodontic treatment and severe apical root resorption sustained a subluxation injury to tooth 22, leading to pulp necrosis and apical pathosis. Initial endodontic management with ProRoot MTA achieved favorable outcomes at 6- and 18-month follow-ups. Two-and-a-half years later, secondary trauma occurred. Over the following 18 months, the tooth developed acute symptoms, a periapical lesion, and radiographic signs of MTA disintegration. Endodontic retreatment with Biodentine resolved the symptoms and achieved complete periapical healing, confirmed at 3, 6, and 18 months, and 4 years post-treatment. Conclusion: This case highlights MTA's susceptibility to acidic degradation in compromised conditions and supports Biodentine as a potentially more pH-resistant alternative. Clinicians should be vigilant when treating traumatized, orthodontically compromised teeth and prioritize restorative materials with high stability in hostile environments to minimize treatment failure risk.
CRIS-Team Scopus Importer:2025-12-05
Keywords: Biodentine; dental trauma; endodontic retreatment; mineral trioxide aggregate; orthodontic treatment; subluxation